2020
DOI: 10.1182/blood-2020-141249
|View full text |Cite
|
Sign up to set email alerts
|

The Enhanced Functionality of Low-Affinity CD19 CAR T Cells Is Associated with Activation Priming and Polyfunctional Cytokine Phenotype

Abstract: We have recently described a low-affinity second-generation anti-CD19 Chimeric Antigen Receptor (CAR) (CAT), characterized by faster antigen dissociation rate which showed enhanced expansion, cytotoxicity and anti-tumour efficacy compared with the high affinity (FMC63 based) CAR used in Tisagenlecleucel in pre-clinical models. Furthermore, CAT CAR T cells showed an excellent toxicity profile, enhanced in vivo expansion and long-term persistence in a Phase I clinical study (Ghorashian et al Nature Med 2019). Ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Many efforts are ongoing to enhance CART cell in vivo expansion and anti-tumor activity by using strategies to non-specifically stimulate CART cell proliferation or re-stimulate CART cells after infusion, utilizing synthetic biology or combination therapy to edit their exhaustion pathways or prevent their apoptosis. 32 , 33 However, this often improves CART efficacy at the cost of the CART safety profile: most of these approaches are associated with increased production of inflammatory cytokines and higher risk for the development of CART-associated toxicities such as CRS and NT (efficacy/toxicity linkage). In contrast, our data indicate that GM-CSF knockout in CART cells results in enhanced CART cell proliferation and anti-tumor activity, while being associated with a marked reduction in GM-CSF levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many efforts are ongoing to enhance CART cell in vivo expansion and anti-tumor activity by using strategies to non-specifically stimulate CART cell proliferation or re-stimulate CART cells after infusion, utilizing synthetic biology or combination therapy to edit their exhaustion pathways or prevent their apoptosis. 32 , 33 However, this often improves CART efficacy at the cost of the CART safety profile: most of these approaches are associated with increased production of inflammatory cytokines and higher risk for the development of CART-associated toxicities such as CRS and NT (efficacy/toxicity linkage). In contrast, our data indicate that GM-CSF knockout in CART cells results in enhanced CART cell proliferation and anti-tumor activity, while being associated with a marked reduction in GM-CSF levels.…”
Section: Discussionmentioning
confidence: 99%
“… 32 In a different approach, modification of CART cell activation has been accomplished through modulation of CART cell antigen binding by using a lower affinity single chain variable fragment in the CAR design. 33 However, these strategies – aimed at ameliorating CART cell apoptosis and nonspecifically enhancing their proliferation – are associated with increased inflammatory cytokine secretion and CART cell-associated toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…To the editor, Chimeric antigen receptor (CAR) T-cell therapy produces high response rates in acute lymphoblastic leukaemia (ALL), and while products with 4-1BB costimulatory domains or those with low affinity are persistent, other products have limited response durability without subsequent consolidative allogeneic haematopoietic cell transplantation (al-loHCT). [1][2][3] Unfortunately, many patients with ALL who receive CAR-T cells are ineligible for alloHCT due to failing prior transplant(s), co-morbidities or lack of donors. Tyrosine kinase inhibitor (TKI) therapy has improved the outcomes in Philadelphia chromosome-positive (Ph+) ALL and has been adopted as a maintenance therapy in alloHCT recipients.…”
Section: Tyrosine Kinase Inhibitor Maintenance Following Chimeric Ant...mentioning
confidence: 99%
“…Using CyTOF technology, Michelozzi et al. compared the FMC63 (high-affinity) and CAT (moderate-affinity) CD19 CARTs and found that, after engaging with CD19+ leukemia cells, the CAT CD19 CARTs contained significantly more polyfunctional T cells than the FMC63-derived CARTs ( 160 ). This suggests proper moderate-affinity ABD may allow CARTs to preserve their polyfunctionality, which is important for antitumor effect ( 161 ).…”
Section: The Effects Of Abd Affinity On the Biology And Function Of C...mentioning
confidence: 99%
“…Such transient break during “off” time may rejuvenate and preserve CART function ( 37 ). Similarly, the moderate-affinity CAT mAb has similar K on as high-affinity FMC63, but has much higher K off ( 151 ), which may contribute to the formation of memory T cells and polyfunctionality of CAT CARTs ( 160 ) and durable antitumor effects ( 151 ). Thus, the dwell time and kinetics of ABD-target engagement may be more important than affinity (K D ) in deciding the outcome of CARTs.…”
Section: The K D Kon K ...mentioning
confidence: 99%